D1 Dopamine Receptor Activation Induces Neuronal eEF2 Pathway-Dependent Protein Synthesis - David, Orit; Barrera, Iliana; Gould, Nathaniel; Gal-Ben-Ari, Shunit; Rosenblum, Kobi (Frontiers in Molecular Neuroscience, 2020)
Dopamine, alongside other neuromodulators, defines brain and neuronal states, inter alia through regulation of global and local mRNA translation. Yet, the signaling pathways underlying the effects of dopamine on mRNA translation and psychiatric disorders are not clear. In order to examine the molecular pathways downstream of dopamine receptors, we used genetic, pharmacologic, biochemical, and imaging methods, and found that activation of dopamine receptor D1 but not D2 leads to rapid dephosphorylation of eEF2 at Thr56 but not eIF2 in cortical primary neuronal culture in a time-dependent manner. NMDA receptor, mTOR, and ERK pathways are upstream of the D1 receptor-dependent eEF2 dephosphorylation and essential for it. Furthermore, D1 receptor activation resulted in a major reduction in dendritic eEF2 phosphorylation levels. D1-dependent eEF2 dephosphorylation results in an increase of BDNF and synapsin2b expression which was followed by a small yet significant increase in general protein synthesis. These results reveal the role of dopamine D1 receptor in the regulation of eEF2 pathway translation in neurons and present eEF2 as a promising therapeutic target for addiction and depression as well as other psychiatric disorders.